Comparison investigation of fluid rheological characteristics effect on stator temperature field for large hydro-generator based on experiment. Issue 1 (5th January 2015) - Ahmed Masmoudi, Dr; Ding, Shuye; Wang, Mengqi
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to explore the relationship of fluid flow and heat transfer inside the generator, a large hydro-generator is taken for an example and the temperature field in the generator is calculated according to computation of fluid field by using of corresponding mathematics methods based on fluid mechanical theory and heat transfer theory. Design/methodology/approach – To calculate the temperature field of the generator more accurately, a large-scale hydro-generator is taken as an example and the mathematical model and physical model of 3D stator temperature field and fluid field are established. And the calculation results of the fluid field are applied into the physics field of generator, coupled relationship between fluid field and temperature field was calculated by using of finite volume method and finite element method, respectively. The temperature fields based on fluid fields and the effect of different fluid flow state on generator temperature were analyzed and compared. Findings – The calculated results shows show good agreement with the measured results, meanwhile the effect of different fluid field state on the temperature field is analyzed and the relationship between temperature fields and fluid fields is achieved, which will provide a theoretical basis for ventilation structure design and calculation of synthesis physical fields. Originality/value – The relationship between temperature fields and fluid fields is obtained, providing a theoretical basis for ventilation structure design and calculation of synthesis physical fields.